Pengaruh Pandemik Covid-19 Terhadap Pendapatan Tempat Wisata dan Kinerja Karyawan Pariwisata di Jakarta - Soehardi, Soehardi; Permatasari , Diah Ayu; Sihite, Janfry (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2020)
This study aims to determine the impact of the co-19 pandemic on the tourism industry, especially tourism and entertainment revenue as well as the performance of tourism employees in Jakarta. The research method used is a quantitative research method with composite reliability analysis, cronbach's alpha, average variance extracted, t test and r square using Partial Least Square (PLS) Structural Equation Model (SEM). The population in this study were all tourism employees in Jakarta using simple random sampling data obtained amounted to 93. There is a significant influence of the covid-19 pandemic on the performance of tourism employees in Jakarta. The longer the covid-19 pandemic, the more influence on the decline in the performance of tourism employees. The most dominant of covid-19 pandemic indicator is the inherent risk of covid-19 transmission compared to other indicators such as massive testing, equipment availability and health protocols. The most dominant of employee performance indicator is task performance by way of work from home and work from office when compared to other indicators such as adaptive performance or contextual performance. Temporary closure of tourist attractions and entertainment has a negative impact on the decline in tourism employee performance such as employee reductions, salary deduction and incentives and layoffs. There is a significant influence of the co-19 pandemic on the revenue of tourist attractions in Jakarta. The longer of covid-19 pendemic, the more influence on income decreases tourist attractions. The most dominant indicator of tourist and entertainment revenue is the amount of original regional revenue from the tourism and entertainment tax sector. There is a significant influence of tourist attraction revenue on the performance of tourism employees in Jakarta. Revenue of tourist attractions decreases, then the effect on the decline in the performance of tourism employees. Keywords: covid-19 pandemic, revenue of tourism places and tourism employee performance Abstrak Penelitian ini bertujuan untuk mengetahui dampak pandemik covid-19 pada industri pariwisata, khususnya pendapatan tempat wisata dan hiburan serta kinerja karyawan pariwisata di Jakarta. Metode penelitian yang digunakan adalah metode penelitian kuantitatif dengan analisis composite reliability, cronbach’s alpha, average variance extracted, uji t dan r square menggunakan Partial Least Square (PLS) Structural Equation Model (SEM). Populasi dalam penelitian ini adalah seluruh karyawan pariwisata di Jakarta dengan menggunakan simple random sampling diperoleh data berjumlah 93. Pengaruh yang signifikan pandemik pandemik covid-19 terhadap kinerja karyawan pariwsata di Jakarta. Semakin lama pandemik covid-19, maka semakin berpengaruh pada penurunan kinerja karyawan pariwisata. Indikator pandemik covid-19 yang paling dominan adalah resiko inheren penularan covid-19 dibandingkan dengan indikator lainnya seperti massive testing, equipment availability dan protokol kesehatan. Indikator kinerja karyawan yang paling dominan adalah kinerja tugas atau task performance dengan cara work from home and work from office apabila dibandingkan dengan indikator lainnya seperti kinerja adaptif atau adaptive performance and kinerja kontektual atau contextual performance. Penutupan sementara tempat wisata dan hiburan berdampak negatif pada penurunan kinerja karyawan pariwisata seperti pengurangan karyawan, pemotongan gaji dan insentif serta pemutusan hubungan kerja (PHK). Pengaruh pandemik covid-19 terhadap pendapatan tempat wisata di Jakarta. Semakin lama pendemik covid-19, maka semakin berpengaruh pada penurunan pendapatan pendapatan tempat wisata. Indikator pendapatan tempat wisata dan hiburan yang paling dominan adalah jumlah penerimaan asli daerah dari sektor pajak wisata dan hiburan. Pengaruh pendapatan tempat wisata terhadap karyawan pariwsata di Jakarta. Pendapatan tempat wisata semakin menurun, maka berpengaruh pada penurunan kinerja karyawan pariwisata. Kata kunci: pandemik covid-19, pendapatan tempat wisata dan kinerja karyawan pariwisata.